Association between COMT gene polymorphisms, clinical symptoms, and cognitive functions in Han Chinese patients with schizophrenia. (June 2018) - Sun, Zuoli; Zhang, Zhengrong; Mao, Peixian; Ma, Yun; Li, Wenbiao; Li, Jun; Yang, Xue; Ling, Sihai; Tang, Yilang
Abstract : Aim: Catechol- O -methyltransferase (COMT) gene variants may be involved in the pathogenesis of psychotic symptoms, and associated especially with negative symptom in schizophrenia, but their roles in cognitive function and treatment response remain unclear. The aim of this study was to explore the association between COMT gene polymorphisms, clinical symptoms (including cognitive function), and treatment response to antipsychotic medications in patients with schizophrenia. Patients and methods: A total of 200 Han Chinese inpatients with schizophrenia were recruited in accordance with Diagnostic and Statistical Manual of Mental Disorders, 4th ed. (DSM-IV). In total, 96 of them completed assessments at baseline and after 8 weeks of antipsychotic treatment. Clinical symptoms were assessed using the Positive And Negative Syndrome Scale (PANSS), and cognitive function was evaluated using the Verbal Fluency Test, Trail Making Test A-B, Stroop Color-Word Test, and Wisconsin Card Sorting Test. Two single nucleotide polymorphisms, rs4680 and rs165599, on the COMT gene were genotyped. Results: At baseline, we found no significant genotypic association between rs4680 and clinical symptoms or cognitive function. After 8 weeks of antipsychotic treatment, compared with patients with GG genotype, patients with AA/AG genotypes at rs4680 showed significantly higher scores on PANSS total, both at baseline and at the end of 8 weeks, especially in negative and general psychopathology symptoms. Patients with GG at rs165599 scored significantly higher on the Stroop test, suggesting better cognitive performance after 8 weeks of treatment. No significant association was found between rs165599 genotype and psychiatric symptoms as assessed by the PANSS and cognitive function tests at baseline. Conclusion: Our findings suggest that the COMT gene polymorphisms may influence the response to antipsychotic treatment in Han Chinese patients with schizophrenia.